Tác động của giá dầu lên lượng khí thải CO2 tại Việt Nam: Liệu có tồn tại hiệu ứng bất đối xứng? - Nguyễn Huy , Bá (JOURNAL OF ASIAN BUSINESS AND ECONOMIC STUDIES, 2024)
This study investigates the asymmetric effects of oil prices on  emissions in Vietnam by using the Non-linear Autoregressive Distributed Lag (NARDL) approach with annual data on real crude oil prices, energy consumption, real per capita income and  emissions in the period 1984–2021. The important results are in threefold.  First, oil prices have a significant negative impact on  emissions in the long term, specifically, an increase in oil prices contributes to reducing  emissions and a decrease in oil prices increases  emissions, which causes environmental pollution. Second, an increase in oil prices has a stronger influence than a decrease in oil prices on  emissions, which implies the existence of an asymmetric effect of the impact of oil prices on  emissions in the long term. Third, in the short term, the asymmetric impact of oil prices on emissions has the opposite trend compared to the long term. These findings are considered a meaningful reference source for using energy efficiently and minimizing  emissions to improve environmental quality.
Keywords: Oil Prices; CO2 Emissions; Energy Consumption; Pollution; Non-linear ARDL; Asymmetric Relationship